Testing the generalized validity of the emotion knowledge test scores - Delgado, Ana R. (2018)
Differential item functioning (DIF) is of the utmost importance in order to corroborate the generalized validity of test scores in different groups. DIF indicates that an item does not function equally in different groups such as age, gender or cultural ones. Our objective was to contrast the generalized validity of the Emotion Knowledge (EK) test scores in a heterogeneous Argentinian sample composed of 100 females and 100 males (age range: 18-65). Data from the original validation sample (200 Spanish participants, half of them males) were conjointly analyzed (total n = 400). Results of the Rasch Model (RM) analysis indicated that both fit to the RM and reliability (ISR = .97, PSR = .80) were adequate. Item logit measures ranged from-3.89 to 3.68, and person logit measures ranged from-1.12 to 5.09, with a mean value of 2.36. DIF was tested for gender, age, educational level and country, with a few item contrasts found to be statistically significant. Even though small significant differences in EK scores were associated with educational level (d = .25) and country (d =-.25), they became non-significant after removing the seven country-related DIF affected items. We can conclude that there is enough evidence for the generalized validity of EK test scores in Argentina. Given that recent theories of human emotion consider conceptual knowledge supported by language as constitutive of emotions, the EK test can be used in academic or applied settings where individual differences in emotional competence might be relevant.